A right to lie? : presidents, other liars, and the First Amendment - Ross, Catherine J. (University of Pennsylvania Press, 2022)
"Is there any way to stop a president who lies constantly about matters large and small, who regularly displays his disconnection from facts or verifiable reality, and whose lies endanger the nation and threaten the very foundations of democracy? This book approaches that question and more by examining how the First Amendment treats deception in public life. President Donald J. Trump's mendacity during his term in office and its consequences for the nation highlighted the urgent need to grapple with lies by public officials and in public debate. But this book is not just about Trump and it is not just about presidents. As I delve into the First Amendment's treatment of deception I will introduce a range of characters from every walk of public life in situations that implicate factual falsehoods and freedom of expression. They include: a minor public official masquerading as a Medal of Honor recipient, purveyors of birtherism, and candidates for office who falsely malign their opponents or even usurp the names of famous people. Their stories, and the outcomes of the resulting court cases, reveal the almost insurmountable constitutional and practical hurdles facing efforts to rein in public deception. The freedom of speech guaranteed by the First Amendment expressly aims to protect unorthodox thought-unpopular views and the ideas of dissidents, which majorities are prone to label "false." A serious tension exists between protecting free speech under the First Amendment and combatting the spread of falsehoods that can endanger a free society"--